Controlled morphology of MWCNTs driven by polymer-grafted nanoparticles for enhanced microwave absorption. Issue 33 (7th August 2017) - Yun, Seokjin; Kirakosyan, Artavazd; Surabhi, Srivathsava; Jeong, Jong-Ryul; Choi, Jihoon
Abstract : A simple and robust platform, based on polymer-grafted nanoparticles to facilitate a controlled morphology of nano-fillers, provides a route for strategically designing nanostructured EM wave absorbers with a percolated MWCNT network as well as a controlled NP arrangement. Abstract : The development of a lightweight electromagnetic (EM) wave absorber with a wider bandwidth and reflection loss at a low loading is of great interest for applications ranging from conventional electronic devices to specific devices or instruments of the military and aerospace. Although nano-filler ( i.e. carbon nanotubes, magnetic nanoparticles, etc. ) based polymer nanocomposites (PNCs) have shown great promise in this area of research, typically poor control of their surface modification and dispersion has prevented further development of these materials for application in EM wave absorbers. Here, we introduce and demonstrate a simple and robust platform based on polymer-grafted nanoparticles to facilitate a controlled morphology of nano-fillers, providing a route for strategically designing nanostructured EM wave absorbers with a percolated MWCNT network as well as a controlled NP arrangement. At equal loadings of nano-fillers (1 wt% of MWCNTs), much deeper reflection loss (RL = −26.9 dB at 5.4 GHz) and a wider bandwidth (4.9 GHz for RL < −10 dB) are observed compared to the conventional PNCs. We show that polymer-grafted nanoparticles serve as a matrix for unfunctionalized CNTs and show a much enhanced dispersion of CNTs, providing a novel opportunity for the multi-functional PNCs by combining functions arising from the controlled dispersion of heterogeneous materials ( i.e. inorganic nanoparticles and CNTs) in a new type of CNT/NP/polymer nanostructure.